ISOLASI, IDENTIFIKASI DAN UJI AKTIVITAS ANTIBAKTERI MINYAK ATSIRI DARI KULIT KAYU AKWAY (Drimys arfakensis Gibbs) ASAL PEGUNUNGAN ARFAK PAPUA - Hajjah Lita Chilviana Hajjah Lita Chilviana; Bimo Budi Santoso; Evelina Somar (FMIPA Universitas Papua, 2022)
ABSTRACT Isolation of essential oil by steam and water distillation method, identification by GC-MS and antibacterial activity test against essential oil of akway bark (D. arfakensis Gibbs) have been carried out. The results showed that the essential oil component of akway bark was composed of 142 compounds, which were dominated by 10 components. The ten suspected components are: 4,5-dimethyl-1-heksen (4,15%); 4-methyl-1-ol-3-penten (3,93%); 1,4-benzodioksan-2,3-diyldiacetate (3,59%); (E) 2,6-dimethyl-1,6-diol-2,7-octadene (3,32%); 1[5(1-Hidroxyethylidene)-1,3-cyclopentadien-1-yl]-ethanone; (3,28); 2-(2,5-hexadiynyloxy)tetrahydro-2H-pyran (3,08%); 3,7-dimethyl-1,6-octadiene (3,03%); 2-methyl-2-ol-4-penten (2,52%); 3-methyl-1-ol-4-penten (2,51%); 4,8-dimethyl-4-ol-1,7-nonadien (1,85%). Testing the antibacterial activity of Akway bark (D. arfakensis Gibbs) using the well diffusion method against four test bacteria, namely B. subtilis, E. coli, S. aureus, and S. typhi, showed that Akway essential oil (D. arfakensis Gibbs) had Inhibition with strong to very strong category. The inhibition of essential oils against the test bacteria B. subtilis, E. coli, S. aureus, and S. typhi, each had inhibition zones of 25 mm, 16.5 mm, 34 mm, and 22 mm. Keywords: D. arfakensis Gibbs., B. Subtilis, E. Coli, S. aureus, S. typhi and essential oil composition.